Effect of Alkyl Chain Length on the Sensitizing Action of Substituted Non‐Symmetric Squaraines for p‐Type Dye‐Sensitized Solar Cells. Issue 9 (9th June 2017) - Bonomo, Matteo; Saccone, Davide; Magistris, Claudio; Di Carlo, Aldo; Barolo, Claudia; Dini, Danilo
Abstract: The design and the synthesis of three unsymmetrical squaraines, DS_34, DS_45, and DS_47, have been achieved for their utilization as sensitizers of screen‐printed NiO cathodes in p‐type dye‐sensitized solar cells (p‐DSCs). DS_34, DS_45, and DS_47 are bidentate dyes, each bearing two carboxylic anchoring groups, which differ solely in the length of alkyl chain attached to the nitrogen atom of the condensed pyrrole ring (ethyl, butyl, and dodecyl for DS_45, DS_34, and DS_47, respectively). The photoelectrochemical properties of the corresponding p‐DSCs are compared and analyzed in terms of the structural differences of DS_34, DS_45, and DS_47. The benchmark dye, p‐SQ2, has also been employed as a p‐DSC sensitizer for the sake of comparison. Current density−voltage ( JV ) curves and incident photon‐to‐current conversion efficiency ( IPCE ) spectra revealed the major efficaciousness of the DS_45 as a dye‐sensitizer, as it was the only system that produced a p‐DSC surpassing 0.04 % of overall efficiency ( η ). This finding was attributed mainly to the larger surface concentration of chemisorbed DS_45 with respect to the other squaraines. Abstract : Dying to be seen : p‐Type solar cells are sensitized with three different squaraine dyes. Current density−voltage curves are measured for the cells with DS_45 (red), DS_34 (blue), and DS_47 (green). It is found that the shorter the side chain (C2 H5, C4 H9, and C12 H25, respectively), the higher the short‐circuit density and the photoelectric conversion efficiency. Incident photon‐to‐current conversion efficiency spectra (inset) reveal that the dyes adsorb the near‐IR region of the solar radiation spectrum.